2017
DOI: 10.1017/s1751731116001701
|View full text |Cite
|
Sign up to set email alerts
|

Changes in milk performance and hepatic metabolism in mid-lactating dairy goats after being fed a high concentrate diet for 10 weeks

Abstract: Feeding a high concentrate (HC) diet is a widely used strategy for supporting high milk yields, yet it may cause certain metabolic disorders. This study aimed to investigate the changes in milk production and hepatic metabolism in goats fed different proportions of concentrate in the diet for 10 weeks. In total, 12 mid-lactating goats were randomly assigned to an HC diet (65% concentrate of dry matter, n = 6) or a low concentrate (LC) diet (35% concentrate of dry matter, n = 6). Compared with LC, HC goats prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…In dairy production, dairy cows are commonly fed HC diet to meet the needs of energy and nutrients during lactation to increase milk yield. In this study, the milk yield in the HC group was higher than that in the LC group, which was consistent with the results of previous studies [ 31 , 32 ]. Although HC diet increased milk yield of dairy cows, it resulted in adverse effects on milk components.…”
Section: Discussionsupporting
confidence: 93%
“…In dairy production, dairy cows are commonly fed HC diet to meet the needs of energy and nutrients during lactation to increase milk yield. In this study, the milk yield in the HC group was higher than that in the LC group, which was consistent with the results of previous studies [ 31 , 32 ]. Although HC diet increased milk yield of dairy cows, it resulted in adverse effects on milk components.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we further investigated hepatic morphology and metabolism. Previous studies reported that high concentrate diet can induce TG accumulation, in ammation, and tissue damages in ruminants (Dong et al, 2017, Guo et al, 2017. Although no obvious in ammation, steatosis, and damages were shown in HE staining sections, we observed remarkable glycogen deposition in HC group via PAS staining.…”
Section: Discussioncontrasting
confidence: 50%
“…Unlike non-ruminant mammals, ruminants primarily depend on hepatic gluconeogenesis as their source of glucose to meet their energy demand (Overton et al, 1999). Dong et al found that high concentrate diet signi cantly increased the enzyme activities involved in glucogenesis, including G6PC and PCK1, whereas no obvious changes in the enzyme activities involved in glycolysis (Dong et al, 2017). It is highly consistent with our data, high concentrate diet signi cantly up-regulated the expression of G6PC and PCK1 at gene and protein levels, however, the other genes involved in glycolysis and glucose transport did not show statistical signi cance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations